Eurosteoporosis: A Novel Proposal for a Discussion on the Acting Level of the European Union in the International Politics - Arman, Murat Necip (2012)
This study claims that the state of "Eurosclerosis" experienced in the European Union countries has been transformed into to "Eurosteoporosis" as a result of developments resulting from several causes. As the European Union´s ability to solve the problems today it faces decreases, the prominence of its functional disability in institutional meaning and the ineffectiveness of steps taken to overcome problems incresase the concerns about the future of the European Union. It is not possible to claim that the European Union has undergone such a transformation that it can overcome the robust problems of the millenninum through the reforms after the Lisbon Treaty. The developments in international politics in the 2000s and the effects of the global financial crisis that the emerged after 2008 triggered the state of "Eurosteoporosis". Resumo Este estudo afirma que o estado de "Eurosclerosis" experienciado nos países da União Europeia foi transformado em "Eurosteoporose", como resultado de desenvolvimentos resultantes de várias causas. Como a capacidade da União Europeia para resolver os problemas atuais enfrenta decréscimos, a proeminência da sua deficiência funcional em termos institucionais e a ineficácia das medidas tomadas para superar os problemas aumentam as preocupações com o futuro da União Europeia. Não é possível afirmar que a União Europeia sofreu uma transformação que possa ultrapassar os problemas robustos do milénio através das reformas após o Tratado de Lisboa. Os desenvolvimentos na política internacional nos anos 2000 e os efeitos da crise financeira global que surgiram depois de 2008 desencadearam o estado de "Eurosteoporose".